Recycling of the biomass waste defatted almond meal as a novel nutritional supplementation for cultivated edible mushrooms - Pardo-Gimenez, Arturo; Carrasco, Jaime; Maria Roncero, Jose; Alvarez-Orti, Manuel; Zied, Diego Cunha [UNESP]; Emilio Pardo-Gonzalez, Jose (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2018)
Defatted almond meal (DAM) is an useless biomass waste obtained after oil extraction. The substrate designed for mushroom cultivation is achieved through a controlled composting process from agricultural by-products (chicken manure and wheat straw). This work shows the potential of DAM as efficient compost supplement for culturing the species Agaricus bisporus (J.E. Lange) Imbach and Pleurotus ostreatus (Jacq.) P. Kumm. Supplementation during A. bisporus cultivation results in larger mushrooms with a firmer texture and higher dry matter and protein contents in comparing with the non-supplemented substrate. In P. ostreatus, supplementation at a dosage of 15 g kg(-1) provided a yield improvement up to 31.8%, compared to the control without supplement. The supplementation with DAM supposed equivalent or better yield than the commercial supplements. Therefore, the technique developed assessed good agronomic potential for application of DAM at the commercial scale in P. ostreatus cultures, adding value to a worthless organic by-product.
Keywords: defatted almond meal; yield, quality; Agaricus bisporus; Pleurotus ostreatus; recycled waste